A hybrid stochastic domain decomposition method for partial differential equations with localised possibly rough random data. Issue 1 (17th December 2018) - Gruhlke, Robert; Eigel, Martin; Hömberg, Dietmar; Drieschner, Martin; Petryna, Yuri
Abstract: The presence of air voids in adhesive bonds, possible introduced in a manufacturing process, is regarded as one main reason for failure of rotor blades. Building up a model for material with random inclusion, we numerically solve for it with the help of domain decomposition techniques. This introduces a hybrid method which combines advantages of sampling and stochastic Galerkin strategies based on generalized multi‐element polynomial chaos expansion (gHPCE).